SOSIALISASI PEMETAAN KLASTERISASI INDUSTRI KECIL DAN MENENGAH (IKM) DI KABUPATEN BIREUEN: - - azka rizkina; Sri Wahyuni; M Rasyidin; M Saleh; Mahdi Mahdi (LPPM Universitas Al Muslim, 2021)
Small and Medium Enterprises (SMEs) is an industrial sector that carries out activities in the form of producing various types of products that can grow the economy. Bireuen Regency is an area that has great potential in the development of SMEs. However, so far, SMEs are still running independently, making it difficult for SMEs to meet their needs within a certain period of time, such as limited access to raw materials which sometimes have to be imported from outside Bireuen Regency and even from outside Aceh Province, which in the end will harm SMEs due to backorder. Through industrial clustering, specific or similar SMEs will strengthen each other in a supply chain network, the process of creating value-added with the geographical proximity factor. The academic team of Al Muslim University with Bappeda collaborated in the socialization of